Do ginger extract, natural honey and bitter chocolate remineralize enamel surface as fluoride toothpastes? an in-vitro study - KARGÜL, BETÜL; TAĞTEKİN, DİLEK; PEKER, MEHMET SERTAÇ (Wolters Kluwer Medknow Publications, 2021)
Background: In recent literatures, much attention has been given to natural products for their health benefits. Aims: In this study, the objective was to measure the efficacy of the ginger-honey-chocolate mixture as the remineralization effect has been shown in the literature previously and to evaluate the individual contributions of this mixture; ginger, natural honey, bitter chocolate separately on remineralization of initial enamel caries lesion. Materials and Methods: All specimens were divided into eight groups as: Ginger (Arifoglu®, Turkey) in powder form, (n = 8); Ginger-Honey-Chocolate (n = 8); Natural honey (Balparmak Plateau Blossom Honey®, Turkey) (n = 9); Bitter chocolate (Nestlé®, Switzerland) (n = 8); MI Paste (GC, Japan) (n = 8); Paradontax (Sensodyne, Glaxosmithklein, USA) (n = 9); Pronamel (Sensodyne, Glaxosmithklein, USA) (n = 9); Control (n = 9) groups. Samples were carried out five pH cycles along 7 days at 37°C for each group. During pH cycling, blocks were put in a demineralization (6 h) and a remineralization solution (18 h). The treatment consisted of 1 min. interaction of enamel surfaces with agent/deionized slurries (1:3 w/w) on a daily basis. The surface microhardness (SMH) was determined before and after pH cycling with a Digital Micro-Vickers Hardness Tester (Wilson Wolpert; Europe BV, 401 MVD, Netherlands). Mineral changes were determined by using FluoreCam® and recovery values were calculated as SMHR% and FΔ%, respectively. Results: All groups showed an enhanced remineralization. There was no significant difference in terms of FΔ% (F = 1.223, P = 0.304) and SMHR% (F = 0.709, P = 0.664) between all groups. Conclusion: The herbals (ginger, honey, and bitter chocolate) examined in this study gave promising results with a high remineralization potential. © 2021 Wolters Kluwer Medknow Publications. All rights reserved.
Keywords: Bitter chocolate; Fluoride toothpaste; Ginger; Honey; Remineralization